Fluid Intake and Hydration Strategies of Bodybuilders In the Capricorn District, Limpopo Province, South Africa - Masoga, Sylven; DuToit, Elmine; Coetzee, Frederik; Schall, R (Journal Coaching Education Sports, 2024)
Background: Bodybuilding athletes in Capricorn district of Limpopo province adhere to various hydration practices. However, the extend at which these athletes adhere to the fluid intake and hydration guidelines during sport engagement is unknown. Research objectives: This study aimed to determine the fluid intake and hydration practices of bodybuilders in Capricorn District of Limpopo province and adherence to the guidelines thereof. Furthermore, to investigate the association of fluid intake with the demography of athletes. Methods: A quantitative descriptive study was used to obtain 66 part-time bodybuilders in the Capricorn district. Demographic information and hydration practices of the athletes were collected during training days. Descriptive statistics were used to summarize the athletes' fluid intake and hydration practices. Pearson's correlation test was used to associate hydration practices with the athletes' educational status and source of hydration information. Athletes were 24 (± 4.2) years old, engaged as bodybuilders for 2.3 (± 1.5) years, training once a day (61%), for 2.2 hours (males) and 2.0 hours (females). Athletes used pure water before (51%), during (47%) and after training (57%). Social media (47%) and the internet (25%) were used as sources of hydration information. There was no significant correlation between hydration practices and demographics. Conclusion: Fluid intake of athletes was suboptimal. Athletes consumed mostly pure water before, during, and after their training sessions. Therefore, athletes’ fluid intake (amount) and hydration strategies (type and timing of fluid) did not adhere (mostly suboptimal to) sports nutrition standards. This poses a risk for dehydration during sport.